The case for Culturally and Linguistically Relevant Pedagogy: Bilingual Reading to learn for Spanish-Speaking immigrant mothers. (December 2020) - Ramírez, Andrés
Abstract: Michael Halliday's threefold language learning principle, "learning language, learning through language, and learning about language" (Halliday, 1993), is an important yet underused insight for pedagogy. Equally important are the learning principles of inclusion and social justice advanced by Culturally Relevant Pedagogy (CRP) educators such as Gloria Ladson-Billings (1992; 1995). Based on Halliday and Ladson-Billings premises, a bilingual English-Spanish adaptation of the SFL-based Reading to Learn (R2L) approach (Rose, 2018) is described through a curricular unit focusing on procedural texts in the context of an ESL family literacy program for immigrant Spanish-speaking mothers in Southeast USA. Informed by an adaptation of the preview-view-review bilingual curricular cycle to systematically use native and target language for content, genre, and language instruction, the article focuses on detailing R2L's culturally and linguistically relevant curricular progression -Preparing to Read, Joint Construction, and Independent Construction-as well as the patterned language shifts that led these adult learners to produce rich genre-appropriate procedural texts in English. Crucially, this study proposes the adoption of Culturally and Linguistically Relevant Pedagogy (CLRP) through the use of 'generative genres' as a way to not only to counteract the current marginalization of CRP by standardized curriculum advanced by neoliberal imperatives (Sleeter, 2012) but as a way to better serve Emergent to Advanced Bilinguals (EABs) with an emphasis on adult English learners. The newly proposed CLRP paradigm is guided by core principles of CRP, but enhanced by linguistic principles and meaning making practices advanced by Systemic Functional Linguistics in general and genre-based pedagogy (Rose & Martin, 2012) and Halliday's principles of learning language, learning through language, and learning about language in particular.